2015
DOI: 10.1159/000369472
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Heliox as a Therapy for Acute Respiratory Distress Syndrome in Adults and Children: A Descriptive Review

Abstract: Background: In neonatal respiratory distress syndrome (RDS) and acute RDS (ARDS) mechanical ventilation is often necessary to manage hypoxia, whilst protecting the lungs through lower volume ventilation and permissive hypercapnia. Mechanical ventilation can, however, induce or aggravate the lung injury caused by the respiratory distress. Helium, in a gas mixture with oxygen (heliox), has a low density and can reduce the flow in narrow airways and allow for lower driving pressures. Objectives: The aim of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 52 publications
0
7
0
4
Order By: Relevance
“…In our study, we chose to observe the cases of bronchospasm and wheezing, disorders in which Heliox ® improved gas exchange, decreased respiratory work, and prevented reintubation. ( 33 )…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we chose to observe the cases of bronchospasm and wheezing, disorders in which Heliox ® improved gas exchange, decreased respiratory work, and prevented reintubation. ( 33 )…”
Section: Discussionmentioning
confidence: 99%
“…It was postulated that this may be related to reduction of shear stress and barotrauma with heliox use and its effect on cell‐mediated immunity 7 . However, this effect was not replicated in subsequent studies 8 …”
Section: Commentarymentioning
confidence: 99%
“…This decreased turbulence remained evident even when air ow was restricted, as in the case of obstructive lung disease. Heliox has been applied to various respiratory diseases in adults for more than 70 years with no adverse effectswith no sereous complications reported [6].A case report showed that the combination of helium and oxygen is safe during pregnancy [7].…”
Section: Properties and Safety Of Heliummentioning
confidence: 99%